Comparative analysis of portal hepatic infiltrating leucocytes in acute drug‐induced liver injury, idiopathic autoimmune and viral hepatitis. (April 2015) - Foureau, D. M.; Walling, T. L.; Maddukuri, V.; Anderson, W.; Culbreath, K.; Kleiner, D. E.; Ahrens, W. A.; Jacobs, C.; Watkins, P. B.; Fontana, R. J.; Chalasani, N.; Talwalkar, J.; et al.
Summary Drug‐induced liver injury (DILI) is often caused by innate and adaptive host immune responses. Characterization of inflammatory infiltrates in the liver may improve understanding of the underlying pathogenesis of DILI. This study aimed to enumerate and characterize leucocytes infiltrating liver tissue from subjects with acute DILI (n = 32) versus non‐DILI causes of acute liver injury (n = 25). Immunostains for CD11b/CD4 (Kupffer and T helper cells), CD3/CD20 (T and B cells) and CD8/CD56 [T cytotoxic and natural killer (NK) cells] were evaluated in biopsies from subjects with acute DILI, either immunoallergic (IAD) or autoimmune (AID) and idiopathic autoimmune (AIH) and viral hepatitis (VH) and correlated with clinical and pathological features. All biopsies showed numerous CD8+ T cells and macrophages. DILI cases had significantly fewer B lymphocytes than AIH and VH and significantly fewer NK cells than VH. Prominent plasma cells were unusual in IAD (three of 10 cases), but were associated strongly with AIH (eight of nine) and also observed in most with AID (six of nine). They were also found in five of 10 cases with VH. Liver biopsies from subjects with DILI were characterized by low counts of mature B cells and NK cells in portal triads in contrast to VH. NK cells were found only in cases of VH, whereas AIH and VH both showed higher counts of B cells than DILI. Plasma cells were associated most strongly with AIH and less so with AID, but were uncommon in IAD.